Analisis Dampak Tax Morale Terhadap Kepatuhan Pajak UMKM: Studi Kasus Kota Semarang - Mahmudah, Muslimah; Iskandar, Deden Dinar (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2018)
This study aims to analyze the impact of tax morale on Micro, Small, and Medium Enterprises (MSMEs) tax complianceSemarang City as the case study. This study uses primary data generated from 117 samples of MSMEs in Semarang. Data analysis is performedÂ using binary logistic regression analysis. The results showed that environmental, institutional, ethical, business, and business size variables significantly influence MSMEs tax compliance. On the other hand, variables whose effect on tax compliance is not statistically significant include happiness, religiosity, gender, age, education, and marital status.